DETERMINATION OF COMMUNICATION CLIMATE, COMPETENCE, DISCIPLINE OF EMPLOYEE PERFORMANCE THROUGH WORK SATISFACTION AS AN INTERVENING VARIABLE - Yuritanto, Yuritanto; Rumengan, Jemmy; Indrayani, Indrayani (Zona Manajerial: Program Studi Manajemen (S1), 2019)
This research is a quantitative descriptive study of communication climate, competence, discipline on employee performance through job satisfaction as an intervening variable. This study is to obtain data and information on communication climate, competence, work discipline and employee satisfaction that are used as analysis material to find out its effects on the performance of Tanjungpinang Navigation Class I Office employees. Survey data collection is carried out by utilizing the attitude stage questionnaire that has been adapted for the topic of this research. The number of respondents was 142 people. In order to be able to characterize the attitude, the structural model with Smart PLS 3.2.8 assistive measurement tools is used as a research framework. The results showed that there was a significant relationship between variables Climate communication, Competence, and Discipline on employee performance by 40.3%, and the remaining 59.7% explained by other constructs outside that were examined in this study. The majority of respondents in the research location have insight into addressing this research based on their influence and benefits for employees. The research data shows that it has fulfilled the Composite Reliability assumption with a spread percentage value of 80.6% for the communication climate, 81% for its competence, 79.6% for employee discipline and 85.9% for employee performance and 81% for employee job satisfaction. Showing indicators in each structure have a high-reliability consistency